The Effect of Unit Number Composition (x = 1.5; 1.6; 1.7; 1.8; 1.9; 2.0; 2.1, and 2.2) of Natrium Super Ionic Conductor (NASICON) as Solid Electrolyte on Ion-Sodium Batteries - M. Jahiding; I. N. Sudiana; W. S. Arsyad; L. Rusman; Fitriani; W. D. Triandari; M. A. Mahfud; Y. Milen; J. Wulandari; A. M. R. Akqadri (International Journal of Acta Material, 2024)
The NASICON was originally used more for gas sensors because of its low ionic conductivity, thus limiting its application to sodium-based batteries. In this study, the synthesis of solid-state NASICON in the form (Na1+xZr2SixP3-xO12) derived from Na2CO3, ZrO2, SiO2, and NH4H2PO4, where SiO2, is obtained by extracting from rice husk, then optimized by variating the x value of its composition, with variations of the x values (1,5, 1,6, 1,7, 1,8, 1,9, 2,0, 2,1 and 2,2) selected as a comparison determining the maximum conductivity obtaining from NASICONS, with calcination time ranges of 10 and 7 hours at 1100oC and 1250oC. The results of the analysis of the sample are characterized by specimens showing polycrystalline-shaped diffraction peaks. Furthermore, the characterization results of SEM show a more uniform morphological surface with increased variation of x values used, and the results of EDX analysis show that there are target compounds. Then, characterization using the LCR-Meter shows that the higher thevariation of the x value, the higher the resulting conductivity. NASICON's ionic conductivity in the composition fails to reach the ideal standard of solid electrolyte conductiveness for the application of sodium ion batteries.